Haemodynamic Effects of Sodium–Glucose Cotransporter 2 Inhibitor Treatment in Chronic Heart Failure Patients - C Noah Nilsson; Mads Kristian Ersbøll; Finn Gustafsson (Cardiac Failure Review)
Sodium–glucose cotransporter 2 inhibitors (SGLT-2i) are now recommended in the current European Society of Cardiology/American College of Cardiology guidelines for the treatment of heart failure (HF) across the spectrum of left ventricular ejection fraction (LVEF) and several large trials have documented the beneficial effects of this drug class on cardiovascular outcomes. Although the clinical efficacy of SGLT-2 inhibition in HF is now well recognised, research is still ongoing to better understand the underlying mechanistic effects of this drug class. In this paper we assess the haemodynamic effects following SGLT-2i treatment in HF patients by reviewing the current literature. We focus our review on preload of the LV in terms of filling pressure and pulmonary artery pressure, cardiac output and afterload. We discuss these variables stratified according to HF with reduced LVEF (HFrEF) and HF with preserved LVEF (HFpEF). Finally, we examine the evidence of LV remodelling in the setting of SGLT-2i-related changes in haemodynamics.